Redescription of Notholimnophila Alexander and Acantholimnophila Alexander, poorly known New Zealand endemics (Diptera: Tipulomorpha: Limoniidae) - Ribeiro, Guilherme Cunha (Zootaxa, 2012)
Notholimnophila exclusa (Alexander, 1922) remains the only known species of the genus Notholimnophila Alexander,1924. Acantholimnophila Alexander, 1924 includes two species, A. maorica (Alexander, 1922) and A. bispina (Alexander,1922). These taxa, known exclusively from New Zealand, cannot be properly identified on the basis of available taxonom-ic information, and this situation prevents the advancement of any further studies. In this paper, Notholimnophila and Acantholimnophila are revised and the included species are redescribed and illustrated in detail.